ANALISIS KEPATUHAN KEWAJIBAN PAJAK BENDAHARA DESA DALAM MELAKUKAN PEMOTONGAN PAJAK PADA PEMBANGUNAN INFRASTRUKTUR DI DESA KARANGAN - Dicky Saputra; Poppy Indriani (Institut Bisnis Muhammadiyah Bekasi, 2023)
This study aims to determine the compliance of the village treasurer in making tax cuts on village infrastructure development because we can know that research on cutting each type of tax on village infrastructure development has not been done much, therefore the researchers decided to examine the tax cuts for village infrastructure development in the village. do the Village Treasurer so that there are no tax violations and errors in determining the type and tax rate that are set for deductions for every transaction carried out on village infrastructure development whose funds are sourced from village funds.The method used in this research is a qualitative descriptive research method to reveal events or facts, circumstances, phenomena, variables, and circumstances that occurred during the research by presenting what actually happened. From the results of data analysis conducted by researchers, it is known that the Karangan Village treasurer has applied the type of tax, the determination of the tax rate imposed on every transaction carried out in the infrastructure development process, namely the 379 Meter long footpath has been carried out correctly in accordance with the applicable tax laws. The findings in this study are limited because in Karangan Village, developing village infrastructure does not use construction services but uses a self-management system, it can be concluded that the type of tax that is set on each transaction is not as much as when using construction services.